Between Art and Teaching: A Study on the Profile of Alumni from Undergraduate Dance Programmes in Southern Brazil - Souza, João; Pereira, Marcelo de Andrade; Icle, Gilberto (Education Policy Analysis Archives, 2015)
The following paper analyses the profile of alumni from undergraduate dance programmes in the state of Rio Grande do Sul, Brazil. We problematise a recurring statement in such documents, that is, the promise that the combination of art and education would guarantee a better professional outlook, appropriate to the world of work. This analysis relies on Michel Foucault's ideas of discursive practice and discusses several concepts in order to understand the education and interrelations which can be read in the documents analysed. The main notion of non-dichotomization between art and teaching is explored in the analysis, with special attention to the discursive movements found therein.